The cliffs - Cawthon, Scott, 1971- (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2021)
"Some things must be learned the hard way...Reed sees an opportunity to teach the school bully not to mess with him, but ends up mangling the lesson. Robert, an exhausted single father, gets a crash course in parenting when he buys a fancy new teddy bear to watch and entertain his young son. Chris, eager to join the Science Club at school, agrees to undergo a grisly experiment to be accepted. But in the malevolent universe of Five nights at Freddy's, there's always an education in pain." -- Back cover.